2001
DOI: 10.1046/j.1365-2443.2001.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Chicken pineal clock genes: implication of BMAL2 as a bidirectional regulator in circadian clock oscillation

Abstract: Background: In a transcription/translation-based autoregulatory feedback loop of vertebrate circadian clock systems, a BMAL1-CLOCK heterodimer is a positive regulator for the transcription of the negative element gene Per. The chicken pineal gland represents a photosensitive clock tissue, but the pineal clock genes constituting the oscillator loop have been less well characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 41 publications
9
52
0
4
Order By: Relevance
“…1B), suggesting a difference in molecular properties between the two BMALs. Higher doses of either BMAL1 or BMAL2 expression plasmid caused slight reduction of transactivation level of the mPer1 promoter as observed for chicken BMAL2 (34).…”
Section: Transactivation Of Period Promoters By Bmal1-clocksupporting
confidence: 53%
See 1 more Smart Citation
“…1B), suggesting a difference in molecular properties between the two BMALs. Higher doses of either BMAL1 or BMAL2 expression plasmid caused slight reduction of transactivation level of the mPer1 promoter as observed for chicken BMAL2 (34).…”
Section: Transactivation Of Period Promoters By Bmal1-clocksupporting
confidence: 53%
“…8, or MOP9, see Ref. 31), a member of bHLH-PAS superfamily, was identified in several vertebrates such as zebrafish (32), human (8,31,33,34), chicken (34), rat, and mouse (35). Like BMAL1, BMAL2 interacts with CLOCK (8,32), binds to E-box (8,34), and induces E-box-dependent transactivation (8,31,32,34,36,37).…”
mentioning
confidence: 99%
“…Molekularny mechanizm pracy oscylatora został opracowany na podstawie badań nad modelami cyjanobakterii, grzybów Neurospora, muszki owocówki i myszy, wykazując, że struktura funkcjonowania oscylatora jest uniwersalna w całym świecie zwierzęcym (16,30,42,50,100). Dotychczas w CCS ptaków zidentyfikowano geny zegarowe: Bmal1, Bmal2, Clock, NPas2 zwany też Mop4 i Rorα -stanowiące pozytywny element systemu kodujący białkowe aktywatory transkrypcyjne; oraz Cry1, Cry2, Per2, Per3, E4bp4 i Rev-erbα -tworzące negatywny element systemu kodujący represory transkrypcji (2,21,28,69,87,93,(96)(97)(98). U ssaków dodatkowo występuje Per1, a u kury i wróbla domowego zidentyfikowano nowy Cry4, który jest homologiem Cry4 u ryb (35,43,50,98).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Geny zegarowe u ptaków posiadają natomiast własną, zróżnicowaną w zależności od gatunku, narządu i wrażliwości na światło, charakterystykę rytmicznej ekspresji. Przykładowo, w oku i szyszynce przepiórki ekspresja mRNA Clock wykazuje wyraźny rytm dobowy indukowany przez światło, zaś w szyszynce kury poziom ekspresji jest stały lub wykazuje bardzo słaby rytm oraz jest niewrażliwy na światło (18,51,69,93,98). Gen Per2 jest regulowany przez światło w szyszynce przepiórki, zaś Per3 nie jest wrażliwy na światło (43,98).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…RNA analysis revealed that expression of BMAL2 transcripts was restricted to the fetal brain and adult liver in humans (Ikeda et al, 2000). Although its physiological function in adult liver is not understood, some evidence suggests that it may serve as a regulator of circadian clock oscillation in brain cells (Okano et al, 2001). Members in this superfamily can be classified roughly into three groups (Hogenesch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%